Body Composition, Muscle Quality and Scoliosis in Female Collegiate Gymnasts: A Pilot Study - Trexler, E. T.; Smith-Ryan, A. E.; Roelofs, E. J.; Hirsch, K. R. (International Journal of Sports Medicine, 2015)
Research has demonstrated an elevated prevalence of body weight concerns and scoliosis among female gymnasts. The purpose of the current pilot study was to evaluate the utility of ultrasonography and dual-energy X-ray absorptiometry (DXA) as practical imaging modalities to measure body composition and spinal curvature variables that may correlate with performance in female collegiate gymnasts (n=15). DXA was used to evaluate body composition and lateral spinal curvature, utilizing a modified Ferguson method. Echo intensity (EI) and cross-sectional area (CSA) of the vastus lateralis were determined from a panoramic cross-sectional ultrasound image. For returning athletes (n=9), performance scores from the previous season were averaged to quantify performance. The average performance score was correlated with lean mass of the arms (R=0.714; P=0.03) and right leg (R=0.680; P=0.04). Performance was not correlated with total mass, fat mass or body fat percentage (P>0.10). Scoliosis was identified in 3 of 15 scans (20%). Echo intensity and CSA of the vastus lateralis were inversely correlated with each other (R=−0.637, P=0.01), but not with other measures of body composition or performance. Results suggest that limb LBM may be a determinant of gymnastics performance, and DXA may provide important health and performance-related information for female collegiate gymnasts.
Keywords: dual-energy X-ray absorptiometry; body fat percentage; ultrasonography; spine; echo intensity